Characterization of soiling on PV modules in the Atacama Desert. (September 2017) - Olivares, Douglas; Ferrada, Pablo; Matos, Camila de; Marzo, Aitor; Cabrera, Enrique; Portillo, Carlos; Llanos, Jaime
Abstract: The soling can negatively affect the performance of photovoltaic systems. We studied the species, which deposit on photovoltaic (PV) modules in northern Chile (Atacama Desert). The environmental conditions are the base for the interaction of dust particles and the module's surfaces. We considered 4 locations for the study. We determined that the particle size of the dust to deposit on PV modules is smaller than 63 μm for all the selected sites. However, the morphology varies from place to place influencing optical response of the modules. After 4 months dust accumulation the transmittance of PV glass reduced by 55%.